Differential Protein Expression in Small Intestinal Neuroendocrine Tumors and Liver Metastases. Issue 4 (April 2016) - Kim, Michelle Kang; Ye, Fei; Wang, Daguang; Cui, Miao; Ward, Stephen C.; Warner, Richard R.P.; Roayaie, Sasan; Shafir, Michail; Schwartz, Myron; Zhang, David; Itzkowitz, Steven
Abstract : Objective: Small intestinal neuroendocrine tumors (SI-NETs) are often detected after they have become metastatic. Using a novel protein array, we identified pathways important in SI-NET metastasis development in surgically resected patients. Methods: Paired primary tumors and liver metastases from 25 patients undergoing surgical resection for metastatic SI-NETs were harvested. Extracted proteins were separated by sodium dodecyl sulfate gel and multiplex immunoblots were performed with 136 antibodies. Significant Analysis of Microarray was used to select for differentially expressed proteins. A tissue microarray was constructed from 27 archived specimens and stained by immunohistochemistry. Results: Comparing primary SI-NETs with matched normal small-bowel mucosa, 9 proteins were upregulated and cyclin E was downregulated. The SI-NET liver metastases demonstrated upregulation of P-ERK and p27 but downregulation of CDK2 and CDC25B. When comparing primary SI-NET with their paired liver metastases, cyclin E demonstrated a significant upregulation in the liver metastasis. Tissue microarray demonstrated higher p38 expression and lower Cdc 25b expression in SI-NETs versus liver metastases and confirmed higher expression of p27 in liver metastases versus normal liver. Conclusions: Few studies have compared protein expression in paired primary and metastatic SI-NETs. Our findings reveal changes in a limited number of proteins, suggesting that these may be targets for therapy.